Optimization of Microalga Chlorella vulgaris Magnetic Harvesting - Maria G. Savvidou; Maria Myrto Dardavila; Ioulia Georgiopoulou; Vasiliki Louli; Haralambos Stamatis; Dimitris Kekos; Epaminondas Voutsas (Nanomaterials, 2021)
Harvesting of microalgae is a crucial step in microalgae-based mass production of different high value-added products. In the present work, magnetic harvesting of Chlorella vulgaris was investigated using microwave-synthesized naked magnetite (Fe3O4) particles with an average crystallite diameter of 20 nm. Optimization of the most important parameters of the magnetic harvesting process, namely pH, mass ratio (mr) of magnetite particles to biomass (g/g), and agitation speed (rpm) of the C. vulgaris biomass–Fe3O4 particles mixture, was performed using the response surface methodology (RSM) statistical tool. Harvesting efficiencies higher than 99% were obtained for pH 3.0 and mixing speed greater or equal to 350 rpm. Recovery of magnetic particles via detachment was shown to be feasible and the recovery particles could be reused at least five times with high harvesting efficiency. Consequently, the described harvesting approach of C. vulgaris cells leads to an efficient, simple, and quick process, that does not impair the quality of the harvested biomass.